Tunneled femoral catheters and tunneled jugular catheters, our experience, efficacy and complications - Iyad Abuward Abu-Sharkh; Suleyka Puello Martinez; Luisa Janeiro Moas; Nisrine Arhda; Manuel Fidalgo Diaz; Anabertha del valle Narvaez Benitez; Rafael Alonso Valente; Candido Diaz Rodriguez (Archives of Clinical Nephrology - Peertechz Publications, 2020)
Background: The replacement of the arterio-venous fistula with PTFE prostheses or central tunneled catheters is increasing due to the early exhaustion of autologous native accesses. The percentage of patients with tunneled catheters as vascular access for hemodialysis reaches between 15 to 25%, therefore, it is essential to improve the techniques used to avoid early and late complications, and to look for other possibilities due to early venous exhaustion. The use of tunneled femoral catheters is increasingly frequent due to the impossibility of using accesses of the superior venous axis. In this work we study and analyze the evolution and complications of tunneled catheters, both jugular and femoral, placed in the period from January 1, 2017 to May 30, 2018 in the Interventional Nephrology Unit, Nephrology Department of the Clinical Hospital of Santiago de Compostela. We also compared the evolution of femoral tunneled catheters with tunneled jugular catheters. Results: Although the number of the sample is small, especially in the group of tunneled femoral catheters, and the results were not statistically significant, clinically it was seen that tunneled jugular and femoral catheters present similar results in the short-medium term. No significant differences were detected in both immediate and late complications between tunneled femoral catheters and tunneled jugular catheters, no differences were detected in catheter infections between the two groups. Conclusion: Tunneled femoral catheters can be an effective and safe alternative in case of non-accessibility to the superior venous axis.